Bench to bedside: mechanistic principles of targeting the RAF kinase in melanoma. (14th October 2014) - Rajakulendran, Thanashan; Adam, David N.
Abstract Melanoma, in its advanced form, is an aggressive cancer with a poor prognosis. To date, no therapeutic modality has afforded a high likelihood of curative outcome, with the exception of early surgical resection in patients diagnosed with local disease. However, recent advances in our understanding of the molecular mechanisms and pathophysiology of melanoma have paved the way towards the development of targeted therapeutics. A central player in melanomagenesis is the RAF family of kinases. Key mechanistic details regarding the regulation of RAF kinases have now begun to emerge. Already, vemurafenib, a tailored kinase inhibitor of aberrant RAF function in melanoma, has led to clinical benefit. Despite vemurafenib's success, acquired resistance to the drug warrants the need for further drug development. In this review, we discuss the critical role of RAF dimerization in both melanomagenesis and resistance to RAF inhibitors such as vemurafenib. We also highlight the potential for inhibitors of RAF dimerization to lead to improved outcomes in patients with advanced melanoma.